BRUCELOSIS EN CHIHUAHUA - VILLALOBOS (Instituto Politécnico Nacional, Escuela Nacional Ciencias Biología, Laboratorio Zoología, CD MEXICO, DF, MEX, 1944)
X-ray studies show that in the majority of silicosis cases the lesions are symmetrical in both lungs; in a few, asymmetry is noted In the latter instances, lesions predominate in the right lung The asymmetry is explained on the basis of differences in o
REV MEX MED
Keywords: BRUCELOSIS, CHIHUAHUA; CIENCIAS MEDICAS; MEDICINA INTERNA; ENFERMEDADES INFECCIOSAS